The Role of Top Management Commitment in Enterprise Architecture Development in Governmental Organizations - Banaeianjahromi, Negin (Complex Systems Informatics and Modeling Quarterly, 2018)
Governmental organizations adopt Enterprise Architecture (EA) not only to enhance their performance and efficiency but also to move toward e-government implementation. The article at hand investigates the EA development obstacles in governmental organizations. An interpretivist paradigm using the Grounded Theory Methodology was selected to carry out this study. The data were collected through semi-structured interviews with 9 governmental organizations in Iran. In total, 17 obstacles were identified. This study revealed the precedence in addressing EA development obstacles and top management commitment category was identified as a category that has the highest impact on the EA projects. It was realized that the commitment that top management levels of the organizations show toward EA development projects, motivates employees to effectively engage with the projects. In addition, a committed top manager assigns adequate resources to the EA project in order to prepare the infrastructure of the company. In this study, government and politics category appeared to be a category of external obstacles that affects most of the other categories directly or indirectly. This study contributes to industry and academia by investigating the EA development obstacles.